Technology Integration and Digital Literacy in Islamic Education Learning - Haerudin; Iffah Khadijah; Usep Suherman; Rahma Dilla Zainuri; Agus Fudholi (Al-Mudarris, 2026)
The integration of technology in Islamic Religious Education (PAI) has become increasingly important in developing students’ digital literacy and supporting Islamic character formation in higher education. This study investigates how technology integration in the PAI Study Program at Universitas Buana Perjuangan Karawang contributes to students’ digital competence, learning engagement, and ethical awareness in Islamic education learning. Using a qualitative case study approach, data were collected through in-depth interviews with lecturers and students, classroom observations, and documentation. The data were analyzed using thematic analysis to identify patterns related to technology use, digital literacy development, and learning interaction. The findings reveal that the use of digital technologies, including laptops, presentation applications, online learning platforms, and educational game-based media, enhances students’ communication skills, creativity, collaboration, and critical engagement in learning. Technology integration also supports the development of responsible and ethical digital behavior aligned with Islamic educational values. However, limitations in infrastructure, internet access, and technological facilities remain significant challenges in optimizing learning effectiveness. This study contributes to the discourse on technology-integrated Islamic education by demonstrating that digital literacy in PAI learning is not limited to technical competence but also includes ethical and character dimensions relevant to the digital era. The findings highlight the importance of balanced technology integration that supports both academic and spiritual development in Islamic higher education.